Chimeric viruses of the insect-specific flavivirus Palm Creek with structural proteins of vertebrate-infecting flaviviruses identify barriers to replication of insect-specific flaviviruses in vertebrate cells. (16th September 2019) - Piyasena, Thisun B. H.; Newton, Natalee D.; Hobson-Peters, Jody; Vet, Laura J.; Setoh, Yin X.; Bielefeldt-Ohmann, Helle; Khromykh, Alexander A.; Hall, Roy A.
Abstract : Here we report the generation of novel chimeric flaviviruses, which express the prM and E proteins of either dengue or Zika viruses on the genomic backbone of Palm Creek virus (PCV), an insect-specific flavivirus. The chimeric virus particles were antigenically indistinguishable from their parental prM–E donors, but were unable to infect vertebrate cells. An additional chimera (PCV structural genes in the backbone of West Nile virus – WNV/PCV-prME) was also unable to infect vertebrate cells, but transfection with RNA from this virus resulted in detectable RNA replication and translation but no infectious virion production. These data suggest multiple blocks at the entry, RNA replication and assembly/release stages of insect-specific flavivirus (ISF) infection in vertebrate cells. Serial passaging of these chimeric viruses in mosquito cells identified amino acid substitutions that may lead to increased replication efficiency. These chimeric viruses provide unique tools to further dissect the mechanisms of the host restriction of ISFs.